Cationic lipid-mediated delivery of proteins enables efficient protein-based genome editing in vitro and in vivo - Zuris, John A; Thompson, David B; Shu, Yilai; Guilinger, John P; Bessen, Jeffrey L; Hu, Johnny H; Maeder, Morgan L; Joung, J Keith; Chen, Zheng-Yi; Liu, David R (Nature biotechnology, 2015)
Efficient protein delivery using cationic lipid transfection reagents enables high efficiency protein-based genome editing in vivo and in vitro . Efficient intracellular delivery of proteins is needed to fully realize the potential of protein therapeutics. Current methods of protein delivery commonly suffer from low tolerance for serum, poor endosomal escape and limited in vivo efficacy. Here we report that common cationic lipid nucleic acid transfection reagents can potently deliver proteins that are fused to negatively supercharged proteins, that contain natural anionic domains or that natively bind to anionic nucleic acids. This approach mediates the potent delivery of nM concentrations of Cre recombinase, TALE- and Cas9-based transcription activators, and Cas9:sgRNA nuclease complexes into cultured human cells in media containing 10% serum. Delivery of unmodified Cas9:sgRNA complexes resulted in up to 80% genome modification with substantially higher specificity compared to DNA transfection. This approach also mediated efficient delivery of Cre recombinase and Cas9:sgRNA complexes into the mouse inner ear in vivo , achieving 90% Cre-mediated recombination and 20% Cas9-mediated genome modification in hair cells.